Leveraging process mining from a Lean Six Sigma perspective - Taouil, Fatima Ezzahra (2025)
This research aims at exploring how Process Mining can enhance or not Lean Six Sigma methodologies in improving the blocked orders management process at Company X. This will be done by comparing standalone LSS against an integrated approach with PM.